Prototyping the complex biological form of the beetle Deltochilum Lobipes via 2D geometric morphometrics landmarks and descriptive geometry for 3D printing. Issue 1 (2nd January 2017) - Rochman, Dina; De Luna, Efraín
ABSTRACT: In this paper, we present research carried out in the Morphometric Laboratory, Institute of Ecology, in Xalapa, Veracruz, México, which consisted of creating a new method that links geometric morphometrics techniques and descriptive geometry. In our new method a collection of five photographs was used to tag each morphological point called "Landmarks" that defines the numerical values of the coordinates "x" and "y" in a Cartesian space to generate through the coordinates "x, " "y" and "z" the geometry of the biological form of a beetle, across surfaces, meshes and solids. In this research we worked with the beetle Deltochilum Lobipes that belong to the Scarabaeidae family. We made two prototypes in 3D printed, from the 2D coordinates of morphological points which were obtained through the tpsDig2 program. This research documents evidence that supports the hypothesis of our project: "the quantitative descriptor of shape and size in 2D, contribute in the modeling of complex geometric structures in 3D". GRAPHICAL ABSTRACT: